Misallocation of talent in competitive labor markets - Daniel Ferreira; Radoslawa Nikolowa (Queen Mary University of London, School of Economics and Finance, 2015)
We develop a model in which competition in the labor market may produce worker-firm matches that are inferior to those obtained in the absence of competition. This result contrasts with the conventional wisdom that competition among employers allocates scarce talent efficiently. In a model in which employers asymmetrically learn about the ability of their workers, we show that constraining labor market competition may be socially desirable precisely because it leads to better talent allocation. The model provides a cautionary counterpoint to one of the most popular arguments against the regulation of pay, i.e., the argument that price-distorting regulation leads to inefficient matches of workers and firms.
Keywords: D82; J31; M5; 330; Labor markets; Asymmetric employer learning; Misallocation; Adverse selection